2009
DOI: 10.1007/s00244-009-9385-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and Resveratrol Supplementation to Rat Dams Treated with Di(2-ethylhexyl)phthalate: Impact on Reproductive and Oxidative Stress End Points in Male Offspring

Abstract: This study was carried out to assess the influence of di(2-ethylhexyl)phthalate (DEHP) alone or associated with antioxidants on the male reproductive system in newborn rats, emphasizing the implications of oxidative stress and hormonal balance during prenatal and early postnatal periods. Wistar females were exposed by oral route to DEHP alone or associated with antioxidants from gestational day 7 to lactational day 2 according to the following treatment regimens: (C) vehicle control (canola oil + 1% Tween-80);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…The increased ROS level has been reported to be associated with the decreasing HMG-CoA synthase expression resulting in the decline of steroidogenesis and testosterone concentration [24]. The activities of enzymes in steroidogenesis were found to be recovered by vitamin C in testes [25]. The HMG-CoA synthase protein expression which increased significantly by TSL-A in this study may contribute to the maintenance of steroidogenesis.…”
Section: Resultssupporting
confidence: 49%
“…The increased ROS level has been reported to be associated with the decreasing HMG-CoA synthase expression resulting in the decline of steroidogenesis and testosterone concentration [24]. The activities of enzymes in steroidogenesis were found to be recovered by vitamin C in testes [25]. The HMG-CoA synthase protein expression which increased significantly by TSL-A in this study may contribute to the maintenance of steroidogenesis.…”
Section: Resultssupporting
confidence: 49%
“…However, resveratrol and vitamin C did not provide any protection against the hepatoxicity of DEHP in rats (Botelho et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, epidemiologic studies have reported links between urinary phthalates (e.g., mono-isobutyl phthalate (MiBP)) and phthalate metabolites (e.g., di-2-ethylhexyl phthalate (DEHP) and dibutyl phthalate (DBP)) with increased levels of lipid peroxidation, inflammation and decreased levels of antioxidants [3234]. Prenatal phthalate exposure was also associated with increased oxidative stress in male rat offspring [35], providing some evidence of fetal programming by phthalate exposure. Limited data, however, are available on the effects of phthalates on isoprostane levels during pregnancy, a particularly sensitive period for phthalate exposure.…”
Section: Introductionmentioning
confidence: 99%